Weakening and strengthening of the Indian monsoon during Heinrich events and Dansgaard‐Oeschger oscillations. (18th February 2014) - Deplazes, Gaudenz; Lückge, Andreas; Stuut, Jan‐Berend W.; Pätzold, Jürgen; Kuhlmann, Holger; Husson, Dorothée; Fant, Mara; Haug, Gerald H.
Abstract The Dansgaard‐Oeschger oscillations and Heinrich events described in North Atlantic sediments and Greenland ice are expressed in the climate of the tropics, for example, as documented in Arabian Sea sediments. Given the strength of this teleconnection, we seek to reconstruct its range of environmental impacts. We present geochemical and sedimentological data from core SO130‐289KL from the Indus submarine slope spanning the last ~ 80 kyr. Elemental and grain size analyses consistently indicate that interstadials are characterized by an increased contribution of fluvial suspension from the Indus River. In contrast, stadials are characterized by an increased contribution of aeolian dust from the Arabian Peninsula. Decadal‐scale shifts at climate transitions, such as onsets of interstadials, were coeval with changes in productivity‐related proxies. Heinrich events stand out as especially dry and dusty events, indicating a dramatically weakened Indian summer monsoon, potentially increased winter monsoon circulation, and increased aridity on the Arabian Peninsula. This finding is consistent with other paleoclimate evidence for continental aridity in the northern tropics during these events. Our results strengthen the evidence that circum‐North Atlantic temperature variations translate to hydrological shifts in the tropics, with major impacts on regional environmental conditions such as rainfall, river discharge, aeolian dust transport, and ocean margin anoxia.